THE ASSOCIATION BETWEEN STRESS MANAGEMENT AND EMOTIONAL WELL-BEING AMONG NURSING STAFF IN SAUDI ARABIA'S MAKKAH HEALTH CLUSTER - Reem Hamzah Alshotiri; Hafizah Che Hassan (World Journal of Advanced Research and Reviews, 2026)
Stress has been among the most widespread occupational risks among nurses, especially in high-demanding healthcare environments like the Makkah Health Cluster in Saudi Arabia. Persistent stress has an adverse effect on emotional health resulting in burnout, decreased job satisfaction, and low-quality patient care. This following systematic review aimed to address the following question: What is the association between stress management interventions and emotional well-being among nursing staff in the Makkah Health Cluster, Saudi Arabia? The goal was to synthesize qualitative data concerning the connection between stress management methods and emotional well-being of nurses in this setting. A systematic search was carried out in databases including PubMed, CINAHL, and Scopus following PRISMA guidelines to identify qualitative studies published in 2015-2025. Inclusion criteria was restricted to studies that are carried out in Saudi Arabia, or are related to the Makkah Health Cluster, that investigated stress management interventions or coping mechanisms among nurses. This review synthesized seven qualitative studies involving nurses working in hospital wards, intensive care unit, and community health care centers in Makkah Health Cluster. The data showed that the emotional well-being was always influenced by the coping practices and stressors. Nurses also identified high workloads, pandemic-related challenges, and Hajj pressures as the major stressors. To address them, the nurses used a combination of problem-oriented approaches (teamwork, task-sharing, etc.), emotional approaches (venting, humor, withdrawal, etc.), and spiritual approaches (prayer, religious reflection, etc.), which offered them resilience and purpose. Positive emotional outcomes were associated with organizational support through visible leadership, equitable distribution of workloads, and uniform policies. In general, the review indicates that management of stress in this situation is best where personal and organizational and cultural supports are used to reinforce and strengthen resilience, job satisfaction as well as workforce retention in Makkah Health Cluster. These findings underscore the necessity of integrating the stress management programs within national healthcare agendas such as the Saudi Arabia vision 2030, whereby the welfare of the nurses should be at the center of sustainable health system practices.